HIF-1α Protects Granulosa Cells From Hypoxia-Induced Apoptosis During Follicular Development by Inducing Autophagy - Tang, Zonghao; Xu, Renfeng; Zhang, Zhenghong; Shi, Congjian; Zhang, Yan; Yang, Hongqin; Lin, Qingqiang; Liu, Yiping; Lin, Fengping; Geng, Baorong; Wang, Zhengchao (Frontiers in Cell and Developmental Biology, 2021)
Owing to the avascular structure of the ovarian follicle, proliferation of granulosa cells (GCs) and development of follicles occur under hypoxia, which is obviously different from the cell survival requirements of most mammalian cells. We hypothesized that autophagy may exert an inhibitory effect on GC apoptosis. To decipher the underlying mechanism, we constructed a rat follicular development model using pregnant mare serum gonadotropin and a cell culture experiment in hypoxic conditions (3% O2). The present results showed that the autophagy level was obviously increased and was accompanied by the concomitant elevation of hypoxia inducible factor (HIF)-1α and BNIP3 (Bcl-2/adenovirus E1B 19 kDa-interacting protein 3) in GCs during follicular development. The levels of Bax (Bcl2-associated X) and Bcl-2 (B-cell lymphoma-2) were increased, while the activation of caspase-3 exhibited no obvious changes during follicular development. However, inhibition of HIF-1a attenuated the increase in Bcl-2 and promoted the increase in Bax and cleaved caspase-3. Furthermore, we observed the downregulation of BNIP3 and the decrease in autophagy after treatment with a specific HIF-1a activity inhibitor (echinomycin), indicating that HIF-1a/BNIP3 was involved in autophagy regulation in GCs in vivo. In an in vitro study, we also found that hypoxia did not obviously promote GC apoptosis, while it significantly enhanced the activation of HIF-1a/BNIP3 and the induction of autophagy. Expectedly, this effect could be reversed by 3-methyladenine (3-MA) treatment. Taken together, these findings demonstrated that hypoxia drives the activation of HIF-1a/BNIP3 signaling, which induces an increase in autophagy, protecting GC from apoptosis during follicular development.